Sleeption: Aplikasi Deteksi Gerakan Video Real-time berbasis Mobile untuk Pemantauan Gangguan Tidur Bayi - Andreanto, Dodik Dwi Andreanto; Muhtadi, Muis; Ariyandi, Haffas Zikri (Universitas Hamzanwadi, 2025)
A baby's quality sleep is very important for his or her growth and development. Infant sleep disturbances have a negative impact on their physical health. Monitoring baby's sleep becomes very important to identify potential sleep disorders and ensure optimal sleep quality for babies. This research aims to build an android application called Sleeption using the waterfall model, a mobile-based baby sleep pattern monitoring application connected to a Raspberry Pi 3 device as an edge computing device. The development phase includes the stages of analysing the needs of parents in monitoring activities, application design, implementation of application design, verification of the success of features in the application, application and application testing along with periodic maintenance on the application. Data collection is done by observation with the development team on the needs of parents in conducting baby sleep monitoring activities. The result of our findings is a mobile application that helps parents in the process of monitoring their baby's sleep activities. The results of black box testing show that the Sleeption application is able to provide accurate and real-time information with a latency of 41 ms about the baby's sleep activity. The application of the Sleeption application helps parents in monitoring their baby's sleep patterns, along with the automation of reports on changes in baby sleep patterns helping parents to identify potential sleep disorders more accurately.